Does strategy instruction on the Rey-Osterrieth Complex Figure task lead to transferred performance improvement on the Modified Taylor Complex Figure task? A randomized controlled trial in school-aged children. Issue 1 (2nd January 2019) - Resch, Christine; Keulers, Esther; Martens, Rosa; van Heugten, Caroline; Hurks, Petra
Abstract: Objective: Providing children with organizational strategy instruction on the Rey Osterrieth Complex Figure (ROCF) has previously been found to improve organizational and accuracy performance on this task. It is unknown whether strategy instruction on the ROCF would also transfer to performance improvement on copying and the recall of another complex figure.Methods: Participants were 98 typically developing children (aged 9.5–12.6 years, M = 10.6). Children completed the ROCF (copy and recall) as a pretest. Approximately a month later, they were randomized to complete the ROCF with strategy instruction in the form of a stepwise administration of the ROCF or again in the standard format. All children then copied and recalled the Modified Taylor Complex Figure (MTCF). All productions were assessed in terms of organization, accuracy and completion time.Results: Organization scores for the MTCF did not differ for the two groups for the copy production, but did differ for the recall production, indicating transfer. Accuracy and completion times did not differ between groups. Performance on all measures, except copy accuracy, improved between pretest ROCF and posttest MTCF production for both groups, suggesting practice effects.Conclusion: Findings indicate that transfer of strategy instruction from one complex figure to another is only present for organization of recalled information. The increase in RCF-OSS scores did not lead to a higher accuracy or a faster copy or recall.